Agama dan Spiritualitas Teosofi di Indonesia: Antara Formalisme dan Subtansialisme - Abdulloh Hadziq; Ita Rodiah (Jurnal Kajian Islam Interdisipliner, 2023)
Seiring perkembangan studi agama, muncul konsep religiusitas dan spiritualitas yang diperdebatkan oleh para ahli. Agama dan spiritual mulai mengalami pemisahan ketika terjadi sekulerisme Barat pada pertengahan abad 19 masehi. Dalam penelitian ini penulis menggunakan jenis penelitian kepustakaan (Library Research). Religiusitas lebih dianggap sebagai suatu yang formal dan instusional, sedangkan spiritualitas dikaitkan dengan sesuatu pengalaman personal dan bersifat fungsional, serta mencerminkan upaya perolehan tujuan dan makna hidup. Spiritualitas dan religiusitas berbeda dari segi konsep, namun aspek tertentu keduanya bersinggungan. Teosofi yang berarti kebijaksanaan Tuhan adalah suatu perkumpulan yang dipelopori oleh madam Helena Petrovna Blavatsky. Substansi dari ajaran agama ialah spiritualitas sehingga agama tidak bisa lepas dari spiritualitas. Agama dan religiusitas merupakan bentuk formal atau institusi untuk menuju spiritualitas. Regiusitas terpaku oleh tatanan yang dibentuk oleh struktur teologi tertentu sedangkan spiritualitas memiliki kehendak bebas. [ As the study of religion developed, the concepts of religiosity and spirituality were debated by scholars. Religion and spirituality began to experience separation when Western secularism occurred in the mid-19th century. In this research, the author uses the type of library research. Religiosity is more considered as something formal and institutional, while spirituality is associated with something personal and functional experience, and reflects efforts to obtain the purpose and meaning of life. Spirituality and religiosity are different in terms of concepts, but certain aspects of both intersect. Theosophy, which means the wisdom of God, is an association pioneered by Madam Helena Petrovna Blavatsky. The substance of religious teachings is spirituality so religion cannot be separated from spirituality. Religion and religiosity are formal forms or institutions of spirituality. Religiosity is fixed by the order formed by certain theological structures while spirituality has free will pioneered by Madam Helena Petrovna Blavatsky. The substance of religious teachings is spirituality so religion cannot be separated from spirituality. Religion and religiosity are formal forms or institutions of spirituality. Religiosity is fixed by the order formed by certain theological structures while spirituality has free will.]